Two new species of Amphinemura (Plecoptera: Nemouridae) from Damingshan National Natural Reserve of Guangxi, China - Mo, Raorao; Wang, Guoquan; Yang, Ding; Li, Weihai (Zootaxa, 2020)
Two new species of the Amphinemurinae genus Amphinemura, A. bifascia sp. nov. and A. bicornata sp. nov. are described from Damingshan National Natural Reserve of central Guangxi Zhuang Autonomous Region of southern China. Their relationships to other similar species in the genus are discussed.